Designing an Interactive Game Prototype as Teaching-Learning English Materials Based on Gamification and Indonesian Local Wisdom: The Initial Stages - Siska Lidya Revianti; Basuki Heri Winarno; Femi Dwi Astuti; Nur Ramadhani (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2023)
The rapid changes in the era of Industrial Revolution 4.0 are an important driving factor in the digital transformation process, including the education sector. There are challenges and also great opportunities to improve the quality of education in Indonesia in the modern world. Nowadays, students can learn independently from various learning sources, including from games (gamification). It is hoped that by combining the gamification strategy, the students will have more motivation to study English in a fun way. This research aims to develop a prototype of 3D interactive computer game which includes the English material and also the local wisdom of Indonesia. This prototype will be used as the alternative in teaching-learning English materials in General English courses. The methodology of this research is ADDIE Instructional Design, which consists of 5 stages, namely: Analysis, Design, Development, Implementation and Evaluation. The Unity game engine is used to create a game called " The Legend of Dewi Rengganis" to learn English in a fun way by taking 5 themes in General English material. The content of the game is inspired by the Story of Dewi Rengganis as one of the local folklores in Indonesia. The local wisdom in the story can be used as a means of demonstrating the uniqueness of Indonesian culture. and supporting tourism programs in Indonesia. Material testing and functional testing will be carried out to see whether this game can be run properly. Multimedia experts, linguists and users (students) will be asked for their feedback by distributing questionnaires and interviews.